The Biblical Book of Daniel : the Catalan Translation by the French Hebraist Maties Delcor. - Ferrer Costa, Joan (IVITRA Research in Linguistics and Literature Ser., 2018)
"Delcor (1919-1992) is responsible for a translation of the 'Book of Daniel', which is the only Catalan version of a book of the Bible produced by a North Catalan author to be included in Fundacio Biblica Catalana's 1968 Bible. This unique circumstance was the inspiration to recover this translation and publish it in a scientific edition collated with the original texts from which Delcor worked. The introduction situates this singular work in the context of the long history of biblical translations in Catalan and offers an exegetical approach to this work that tradition has transmitted in three languages of the ancient world: Hebrew, Aramaic and Greek. English equivalents of all of the texts have been added as a further point of comparison."-- Back cover.